Problem of an optimal discretization in acoustic modelling - A. BRAŃSKI (Archives of Acoustics)
In this paper two new models of an acoustic source in BEM are proposed. For simplicity a plane axisymmetric source is modelled. Up to now, the models consist of elements of the same dimension. Furthermore, the nodes are equi-spaced on each element. In contrast to these models, the first new one is composed of optimal elements on which the nodes are equi-spaced. The second new model is composed of optimal elements too but the nodes on each element are optimal (Tchebicheff nodes). Numerical calculations pointed out that the quality of the new models is better than the known ones.